The case against sugar [compact disc, unabridged] - Taubes, Gary (Random House Audio, 2016)
"Among Americans, diabetes is more prevalent today than ever; obesity is at epidemic proportions; nearly ten percent of children are thought to have nonalcoholic fatty liver disease. And sugar is at the root of these, and other, critical society-wide, health-related problems. With his signature command of both science and straight talk, Gary Taubes delves into Americans' history with sugar: its uses as a preservative, as an additive in cigarettes, the contemporary overuse of high-fructose corn syrup. He explains what research has shown about our addiction to sweets. He clarifies the arguments against sugar, corrects misconceptions about the relationship between sugar and weight loss; and provides the perspective necessary to make informed decisions about sugar as individuals and as a society."--